Обзор видов цикадовых рода элуропсис — Aeluropsis Еm. (Auchenorrhyncha, Issidae) - Логвиненко, В.Н. (Вестник зоологии, 1975)
Aeluropsis novalis sp. n. (described by the materials from the Eastern Ukraine) differs from the related species Ae. taurica (Kusn.) in ring-shaped dorsal processes of penis, flat hind cdge of stylus and wide-rounded apex of anal tube. Ae. midica sp. n. and Ac. kharabachica sp. n. (described from Transcaucasus) are similar to the Caucasus species Ac. transcaucasica (Mel.), differing from it mainly in details of penis and stylus structure: Ae. midica sp. n. has lateral regions of theca protruded along the trunk almost to its middle part; for Ae. karabachica sp. n. a triangular form of lobe developed only in the apical part of the penis trunk is typical.